Cultures in Collision and Conversation Essays in the Intellectual History of the Jews - Berger, David (Judaism and Jewish Life, 2011)
In Cultures in Collision and Conversation, David Berger addresses three broad themes in Jewish intellectual history: Jewish approaches to cultures external to Judaism and the controversies triggered by this issue in medieval and modern times; the impact of Christian challenges and differing philosophical orientations on Jewish interpretation of the Bible; and Messianic visions, movements, and debates from antiquity to the present. These essays include a monograph-length study of Jewish attitudes toward general culture in medieval and early modern times, analyses of the thought of Maimonides and Nahmanides, an assessment of the reactions to the most recent messianic movement in Jewish history, and reflections on the value of the academic study of Judaism.